Cognitive traces of life kinetic exercise in puberty sedentary subjects - Sarikabak, Murat; Hepsert, Sezgin; Donmez, Ahmet; Baykara, Cengiz; Cana, Hasip; Ayranci, Mert; Celebioglu, Hatice Asli (Public Library Science, 2025)
In this study, it was aimed to reveal the effect of regular life kinetic exercises on the concepts of motivation and imagery in sports in puberty period individuals. In the study in which pre-test-post-test control group design was used, 44 students (experiment = 22, control = 22) who were continuing their education in a state secondary school and selected by appropriate sampling method participated. The Personal Information Form, Motivation Scale in Sport and Imagery Inventory in Sport were used as data collection tools. The collected data were analysed using repeated measures analysis of variance. When the results were analysed, it was determined that there were statistically significant differences in the pre-test and post-test mean scores of motivation and imagery in sport. As a result, it can be stated that the life kinetic exercise protocol applied for 8 weeks in sedentary individuals positively predicted motivation and imagery parameters in sports. This result indicates that the related psychological phenomena, which are as important as sport performance in sports, can be positively affected by cognitive and motoric exercise combinations.
Keywords: Brain; Motivation; Sport; Acquisition; Performance; Plasticity; Body